“Kekerasan itu Katarsis dari Patriarki!”: Resistensi pada Kekerasan terhadap Perempuan dalam Praktik Gerakan Sosial Aliansi Laki-laki Baru - Febi Rizki Ramadhan (Antropologi Indonesia, 2017)
This research examines a movement of men’s participation towards the elimination of violence against women in Indonesia known as, Aliansi Laki-laki Baru (later refer as ALB). Using an ethnographic method, this research shows that ALB –as a social movement– could not be understood as a homogeneous and monolithic entity because of its diverse meanings of violence against women that are perceived by the participants. Furthermore, this research addresses the discourse productions as an act of resistance towards patriarchy and hegemonic masculinity. In this paper, I argue, patriarchy and hegemonic masculinity as the ideology of violence against women that are embodied in cultural violence. In doing so, this article shows the interwoven relationship between social movement’s meaning-making towards the focus of the movement and the resistance and its main cause: patriarchy and hegemonic masculinity in the context of ALB’s social movement practices.Key words: Aliansi Laki-laki Baru, cultural violence, hegemonic masculinity, patriarchy, resistance, social movement, violence against women